Pembuatan Peta Administrasi Nagari Muaro Takung melalui Kuliah Kerja Nyata (KKN) Berbasis Sistem Informasi Geografis - Nusvia Zulfa; Najwah Fatimah Azzahra; Abid Alfurqan; Vito Leonando Putra; Randi Purnama Putra (Al-DYAS, 2026)
The availability of accurate administrative maps at the nagari level remains a challenge in supporting regional governance, public services, and development planning. In various regions, spatial information is still managed informally, so it is not yet fully standardized and easily updated. This community service activity aims to produce an accurate and sustainable administrative map of Nagari Muaro Takung through the application of Geographic Information Systems (GIS) in the Kuliah Kerja Nyata (KKN) program. The activity was carried out from January 10 to February 8, 2026, in Nagari Muaro Takung, Kamang Baru Subdistrict, Sijunjung Regency, West Sumatra. Data were collected through field surveys using handheld GPS devices and a participatory mapping approach with nagari officials. The collected data included administrative boundaries, public facilities, road networks, waterways, agricultural land, and livestock areas. Data processing was conducted using ArcGIS 10.8 and QGIS 3.28, and was then validated through the ground-truthing method. The results of the activity showed that 87 coordinate points were successfully collected and processed into a 1:10,000-scale administrative map. The map includes seven jorong, transportation networks, public facilities, agricultural areas, and water elements. In addition to producing a map product, this activity also established a digital spatial database that supports the effectiveness of regional administration and can be updated sustainably. The conclusion of this activity confirms that the integration of GIS and participatory mapping can support data-based regional governance and strengthen students’ contribution to the development of geospatial technology at the local level. The implications of this activity include the use of administrative maps as a basis for decision-making, nagari development planning, and the strengthening of spatial information-based public services.